Conviviality as social practice in business relationships: concepts and insights from a case of expatriates. Issue 3 (23rd September 2020) - Guercini, Simone; Ranfagni, Silvia
Abstract : Purpose: This paper aims to investigate the practice of conviviality as the right setting to explore how social capital interacts with business relationships and in particular how resources impacting business relationships take shape in social relations. Design/methodology/approach: This paper has adopted the single case study method combining in-depth interviews, participant observations and focus groups. The investigated case is an Italian business community located in Hangzhou (China), recognized as one of the most active foreign communities in organizing convivial activities. Findings: The study shows that conviviality contributes to generating resources thereby creating interactions in business relationships via social relations through self-narrative, community feeling and empathy. These resources bear distinguishing features. Based on relationships of trust, they are fitting and mutual knowledge-based resources and they are resources performing a sense of inner time. Originality/value: The paper contributes to the interpretation of the interplay between business relationships and social capital through conviviality and is in line with a direction of research, which is increasingly involving industrial marketing and purchasing (IMP) researchers, which is the analysis of social capital in business networks.